Influence of electrode force on metallurgical studies and mechanical properties of resistance spot welded dual phase (DP800) steel joints. (2020) - Rajarajan, C.; Sivaraj, P.; Seeman, M.; Balasubramanian, V.
Abstract: The DP steels are attractive to automotive sectors due to the improved fuel efficiency, occupant's safety and reducing the car body weight . The resistance spot welding (RSW) most appropriate eco-friendly process for sheet metal and white body car assemblies over fusion welding. The present research work analysis the impact of electrode force on mechanical and metallurgical characteristics of dual phase steel. In this investigation similar joint of DP 800 joints (lap shear and cross shear) specimen fabricated and tensile shear test was evaluated using a universal testing machine. Micro and macrostructure were evaluated optical microscope. The hardness was taken along the weld nugget using Vickers microhardness tester machine. The electrode force was varied at five levels (3.75 MPa to 4.75 MPa). The tensile shear strength is found to be increased with an increase in electrode force up to a certain limit and then it decreases. The microhardness survey revealed that peak hardness in the nugget zone and the hardness is lower in the HAZ. The softening of HAZ is mainly attributed to inter-critical heating during welding, which leads to weld failure.